Knowledge Sharing through Technology 8th International Conference on Information and Communication Technology in Teaching and Learning, ICT 2013, Hong Kong, China, July 10-11, 2013, Revised Selected Papers - Lam, Jeanne; Li, Kam Cheong; Cheung, Simon K. S.; Wang, Fu Lee.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the thoroughly revised selected papers of the 8th International Conference on Information and Communication Technology in Teaching and Learning, ICT 2013, held in Hong Kong, China, in July 2013. The 21 revised papers presented were carefully reviewed and selected from various submissions. The papers are organized in topical sections such as management and application of open education resources, application of ICT in support of knowledge sharing, application of mobile devices and social media to knowledge sharing, knowledge sharing for teaching and learning.
Management and application of open education resources -- Application of ICT in support of knowledge sharing -- Application of mobile devices and social media to knowledge sharing -- Knowledge sharing for teaching and learning.
Keywords: Computer science; Information storage and retrieval systems; Education; Computer Science; Computers and Education; Information Systems Applications (incl. Internet).; User Interfaces and Human Computer Interaction; Information Storage and Retrieval